Cultural Interference on German Language Learning for Tourist Guide in Lombok - Kartika, Ajeng Dianing; Kurniawati, Wisma; Hardika, Meilita (Proceeding of International Joint Conference on UNESA, 2025)
Lombok’s growing prominence as a key destination for German-speaking tourists necessitates a professional corps of local guides proficient in the German language. However, these guides, who are predominantly from a Sasak-Indonesian cultural background, face challenges that extend far beyond mere linguistic acquisition. This article investigates the phenomenon of cultural interference in their German language learning process. The core problem lies in the significant clash between the guides’ native cultural framework, often characterized by indirect communication, communal harmony, and high-context politeness (e.g., basa-basi), and the pragmatic and cultural norms embedded in the German language, which typically values directness, task-orientation (Sachlichkeit), and explicit clarity. This study employs a qualitative, case-study methodology. Data was collected through in-depth, semi-structured interviews with experienced German-speaking tourist guides in Lombok, supplemented by direct observation of guide-tourist interactions. The findings identify specific and recurring areas of interference, most notably in: (1) the execution of speech acts such as refusing, apologizing, and handling complaints; (2) differing perceptions of time (Pünktlichkeit) and scheduling; (3) the appropriate use of formal vs. informal address (Sie/Du); and (4) the handling of personal questions and “small talk” protocols. This interference frequently results in pragmatic failure, which can be misinterpreted by German tourists and, in turn, hinders the guides’ own communicative confidence. This paper concludes that standard German language curricula are insufficient. To be effective, German language pedagogy for Lombok’s guides must evolve from a purely linguistic focus to an integrated, intercultural-pragmatic approach. This approach must explicitly address these specific points of cultural friction to bridge the gap between Sasak and German norms, thereby ensuring true communicative competence in a professional tourism context.